Biduality in Spaces of Holomorphic Functions - Galindo, Pablo; Maestre, Manuel; Rueda, Pilar (MATHEMATICA SCANDINAVICA, 2000)
This paper contains characterizations of the bidual space of some closed subspaces of $\mathcal{H}_b(U)$, the space of holomorphic functions bounded type defined on an open subset $U$ of a Banach space $X$, where $U$ is either a bounded balanced open set or the whole space $X$.